2016
DOI: 10.1002/hbm.23360
|View full text |Cite
|
Sign up to set email alerts
|

Fatigue in Parkinson's disease: The contribution of cerebral metabolic changes

Abstract: Fatigue is a common and disabling non-motor symptom in Parkinson's disease associated with a feeling of overwhelming lack of energy. The aim of this study was to identify the neural substrates that may contribute to the development of fatigue in Parkinson's disease. Twenty-three Parkinson's disease patients meeting UK Brain Bank criteria for the diagnosis of idiopathic Parkinson's disease were recruited and completed the 2-[ F]fluoro-2-deoxy-D-glucose (FDG)-PET scan. The metabolic activities of Parkinson's dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 33 publications
(23 citation statements)
references
References 45 publications
0
23
0
Order By: Relevance
“…These findings are consistent with connectivity between the SNc and insula in mediating salience responses irrespective of motivational valence. Of note, impaired interoceptive sensitivity is a non-motor symptom of PD and fatigue in PD is associated with anti-correlated metabolic changes of the saliency network involving the right insula and DMN (Cho et al, 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…These findings are consistent with connectivity between the SNc and insula in mediating salience responses irrespective of motivational valence. Of note, impaired interoceptive sensitivity is a non-motor symptom of PD and fatigue in PD is associated with anti-correlated metabolic changes of the saliency network involving the right insula and DMN (Cho et al, 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…These observations propose that fatigue in PD might be the expression of metabolic abnormalities and impaired functional interactions between brain regions linked to the salience and other neural networks. 78 As mentioned earlier, increased impulsivity and hypomania are nonmotor symptoms associated with behavioral addictions (e.g., pathological gambling) that may occur with dopamine replacement therapy. Recent studies have shown that metabolic patterns associated with impulsivity and hypomania in PD are mostly found within the fronto-insular network.…”
Section: Blood Flow and Metabolismmentioning
confidence: 94%
“…When investigating fatigue in PD by using 18 F‐FDG‐PET, results revealed that PD patients with higher levels of fatigue showed anticorrelated metabolic changes in cortical regions associated with the salience (i.e., right insular region) and default (i.e., bilateral posterior cingulate cortex) networks. These observations propose that fatigue in PD might be the expression of metabolic abnormalities and impaired functional interactions between brain regions linked to the salience and other neural networks …”
Section: Molecular Imaging Of Pdmentioning
confidence: 99%
“…Fatigue is a common nonmotor symptom in PD. Recent studies have reported that PD patients with higher level of fatigue may show anticorrelated metabolic changes in cortical regions associated with the salience (i.e., right insular region) and default (i.e., bilateral posterior cingulate cortex) networks . Other studies of dopaminergic and serotoninergic function in PD patients with and without fatigue demonstrated a serotoninergic denervation in the basal ganglia and related limbic circuits .…”
Section: Behavioral and Affective Complications In Pdmentioning
confidence: 97%